Psychographic Impact on Preference and Satisfaction on Investment Products - Ravindran, Dr. D (International Journal of Psychosocial Rehabilitation, 2020)
–In current global economic situation, financial stability is not only expected for business people but also for the general people including salaried, business and retired ones. Savings and investments are mostly confused and sometimes considered as a synonym. Investment in specific aims at expected multiplication of the amount of money in some period of years with the currently available excess money in hand.This research paper attempts to identify the investment preference and satisfaction on the various avenues with respect to psychographic factors in Chennai city.